Insulin stimulation of pyruvate dehydrogenase in adipocytes involves two distinct signalling pathways. - Johnson, Sam A (2003)
In isolated rat adipocytes, the insulin stimulation of pyruvate dehydrogenase can be partially inhibited by inhibitors of PI3K (phosphoinositide 3-kinase) and MEK1/2 (mitogen-activated protein kinase/extracellular signal-regulated kinase kinase). In combination, U0126 and wortmannin completely block the insulin stimulation of pyruvate dehydrogenase. It is concluded that the effect of insulin on pyruvate dehydrogenase in rat adipocytes involves two distinct signalling pathways: one is sensitive to wortmannin and the other to U0126. The synthetic phosphoinositolglycan PIG41 can activate pyruvate dehydrogenase but the activation is only approx. 30% of the maximal effect of insulin. This modest activation can be completely blocked by wortmannin alone, suggesting that PIG41 acts through only one of the pathways leading to the activation of pyruvate dehydrogenase.